2020
DOI: 10.1088/1755-1315/611/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Scots pine seedling growth stimulants in extreme conditions of the Northern Kazakhstan steppe zone

Abstract: The aim of this research is to determine optimal methods of using stimulants in a pre-sowing treatment of common pine seeds to increase their germination and obtain high-quality planting material. A study has been performed in forest nurseries of the State Forest Natural Reserve (SFNR) “Ertis Ormany” (Pavlodar region) and the Arykbalyk Branch of the State National Natural Park (SNNP) “Kokshetau” (Akmola region). The research is done with one-and two-year-old seedlings of ordinary pine sowing of 2017. A presowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Additionally, extending the propagation period for 'Southern Charm' would reduce the time needed for root development, allowing plants to progress down the production line and sell quicker than the currently suggested propagation window [39]. From our study, it can be concluded that the application method and auxin concentration are entirely species dependent, as has been reported by other researchers [37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, extending the propagation period for 'Southern Charm' would reduce the time needed for root development, allowing plants to progress down the production line and sell quicker than the currently suggested propagation window [39]. From our study, it can be concluded that the application method and auxin concentration are entirely species dependent, as has been reported by other researchers [37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionsupporting
confidence: 69%
“…The rooting process depends on the cutting's diameter and on the nutrients which sustain the biological processes involved in adventitious root formation [65][66][67]. Altogether, it can be concluded that rooting stimulants could have beneficial effects on the development, growth and survival percentage of the plants studied [68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the first 96 Ecuadorian flower companies (Order established according to the income data published by the Superintendencia de Compañías del Ecuador, https://www.supercias.gob.ec/portalscvs/, accessed on 30 April 2021) were chosen. According to the value of sales, these represented approximately 70% of the more than USD 800,000,000 turnover of the sector in 2019 [68]. As seen in Table 5, the turnover in these 96 companies varies from the largest to the smallest, i.e., from USD 12,000 to USD 47,000,000.…”
Section: Case Studymentioning
confidence: 99%
“…The rooting process depends on the cutting's diameter and on the nutrients which sustain the biological processes involved in adventitious root formation [65][66][67]. Altogether, it can be concluded that rooting stimulants could have beneficial effects on the development, growth and survival percentage of the plants studied [68][69][70].…”
Section: Discussionmentioning
confidence: 99%